2013
DOI: 10.1063/1.4846916
|View full text |Cite
|
Sign up to set email alerts
|

Open-loop control of noise amplification in a separated boundary layer flow

Abstract: 1Linear optimal gains are computed for the subcritical two-dimensional separated boundary-layer flow past a bump. Very large optimal gain values are found, making it possible for small-amplitude noise to be strongly amplified and to destabilize the flow. The optimal forcing is located close to the summit of the bump, while the optimal response is the largest in the shear layer. The largest amplification occurs at frequencies corresponding to eigenvalues which first become unstable at higher Reynolds number. No… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 38 publications
(61 reference statements)
4
22
0
Order By: Relevance
“…As pointed out by , the flow response should therefore be dominated by the optimal response. Boujo et al (2013) observed this behaviour in a direct numerical simulation of a different geometry, with a predominance of the optimal response at optimal frequency. As discussed later in section 5, the sensitivity of the stochastic gain is also dominated by the sensitivity of the optimal harmonic gain at the optimal frequency.…”
Section: Harmonic Responsementioning
confidence: 98%
See 3 more Smart Citations
“…As pointed out by , the flow response should therefore be dominated by the optimal response. Boujo et al (2013) observed this behaviour in a direct numerical simulation of a different geometry, with a predominance of the optimal response at optimal frequency. As discussed later in section 5, the sensitivity of the stochastic gain is also dominated by the sensitivity of the optimal harmonic gain at the optimal frequency.…”
Section: Harmonic Responsementioning
confidence: 98%
“…All calculations are performed using methods described in Boujo et al (2013). The finite element software FreeFem++ is used to generate a two-dimensional triangulation of the domain Ω and, based on P2 and P1 Taylor-Hood elements for velocity and presure respectively, to build all the discrete operators involved in calculations of base flow, eigenvalue and sensitivity, from their corresponding continuous expression in variational form.…”
Section: Numerical Methods and Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Such an approach (herein referred to as the base flow approach) offers an attractive alternative to bottleneck "trial and error" procedures, as it allows exhaustive coverage of large parameter spaces at very low computational costs. It has sparked renewed interest in the last decade, through a substantial body of work focusing on steady and unsteady effects modeling the presence of the control cylinder (Giannetti & Luchini 2007;Marquet et al 2008a), and is now routinely applied to a variety of flow configurations (Meliga et al 2010;Pralits et al 2010;Alizard et al 2010) and control targets, including optimal transient growth and optimal harmonic response (Brandt et al 2011;Boujo et al 2013), recirculation length or aerodynamic forces (Meliga et al 2014).…”
Section: Introductionmentioning
confidence: 99%